Foam-mat layer drying of cashew pulp (Anacardium occidentale L.): analysis and evaluation of kinetics - Moura, Luiz Eduardo Freitas de; Paiva, Emanuelle Maria de Oliveira; Freitas, Raul Gomes Leite; Souza, Gabriel Felipe de Vasconcelos; Pereira, André Anderson Costa (Brazilian Journal of Production Engineering, 2026)
Cashew fruit holds great economic and social importance in the development of the Northeast region of Brazil. Despite this, its potential is underutilized due to its high perishability. In this context, foam-layer drying presents itself as an alternative, reducing the amount of water present in the food and preventing the development of microorganisms. Therefore, the objective of this work was to study the kinetics of foam-layer drying of cashew pulp. The experimental conditions of 3, 6, and 8% emulsifier, beating times for foam formation of 5, 10, and 20 minutes, addition of 40% milk, and ultrasonic pretreatment for 2 minutes were evaluated. The fit of kinetic drying models was also assessed, and the Midilli and Weibull models showed an excellent fit. Analyses of the moisture content and water activity of the obtained powders indicated that they are in good condition for storage and subsequent application. Finally, analyses of total phenolic compounds and antioxidant capacity by DPPH and ABTS yielded results of up to 12.55 mg GAE/mg of sample, 44.38 μmol TE/g of sample, and 325.46 μmol Trolox/g of sample.